The association between maternal human papillomavirus (HPV) experiences and HPV vaccination of their children. Issue 4 (3rd April 2021) - Biederman, Erika; Donahue, Kelly; Sturm, Lynne; Champion, Victoria; Zimet, Gregory
ABSTRACT: HPV vaccination prevents most HPV-related cancers yet vaccination rates remain low. In this cross-sectional study, we examined the association between maternal HPV experiences and HPV vaccination uptake among children and whether this association may be explained by perceived benefits of vaccination. We used logistic regression models to estimate the effect of (1) maternal history of abnormal Pap smear, (2), family/friend history of cervical cancer, and (3) maternal history of cervical cancer on HPV vaccination uptake among children. Separate mediation analyses were conducted to determine if perceived benefits mediated the relationship between each maternal HPV experience and HPV vaccination uptake. History of abnormal Pap smear (OR = 1.50, 95% CI = 1.15, 1.97), family history of cervical cancer (OR = 1.72, CI = 1.26, 2.35), and personal history of cervical cancer (OR = 3.00, CI = 1.82, 4.95) predicted HPV vaccination of children. Perceived benefits mediated the relationship between history of abnormal Pap smear (indirect effect =.146, SE =.069, 95% CI =.014, .289), family history of cervical cancer (indirect effect =.228, SE =.079, CI =.080, .387), and personal history of cervical cancer (indirect effect =.298, SE =.116, CI =.082, .533) on HPV vaccination. Our results suggest that personal experiences with HPV-related disease may influence maternal HPV vaccine decision-making.